Bone cemented K-wire fixation versus elastic stable intramedullary nailing fixation of paediatric proximal humerus fractures: A prospective cohort study. Issue 6 (10th February 2023) - Liu, Shibo; Zhang, Yanlong; Cao, Jinchao; Fu, Shijie; Peng, Aqin
Abstract : Background: The objective of this study is to compare the treatments of pediatric displaced proximal humerus fractures with external-fixation technique using the combination of K-wires and bone-cement versus close reduction and internal fixation technique using elastic stable intramedullary nail. Methods: From April 2016 to March 2020, 72 children with proximal humeral fractures were allocated to group A and 44 children with proximal humeral fractures were allocated to group B. Patients in group A were treated with bone-cemented K-wire fixation, and patients in group B were treated with elastic stable intramedullary nailing. The function of the upper limb was assessed using the Shortened Version of the Disabilities of the Arm, Shoulder and Hand questionnaire and Neer score. Patient satisfaction was assessed using the 10-cm visual analogue scale. Results: Bone healing was achieved in group A and B after a mean time of 6.1 ± 1.2 and 6.4 ± 1.1 weeks, respectively. The mean surgical time of groups was 33 ± 9 and 54 ± 12 minutes, respectively. The mean Quick Disabilities of the Arm, Shoulder and Hand questionnaire score of groups were 0.5 ± 1.4 and 0.7 ± 1.5, respectively. Based on Neer score, we obtained 69 excellent and 3 good results in group A, and 41 excellent and 3 good results in group B. There were significant differences regarding duration of operation, cost of treatment, and postoperative angle at bone healing ( P < .05). Conclusions: The external cemented K-wire fixation is a useful and reliable alternative technique for the treatment of severely displaced proximal humerus fractures in children. The technique is a minimally invasive procedure with minimal complications.